REDESIGN OF HORIZONTAL COFFEE ROASTERS WITH TEMPERATURE, TIME AND ROTATION CONTROLS - I Ketut Suherman; I Wayan Suirya; I Made Anom Adiaksa (Logic : Jurnal Rancang Bangun dan Teknologi, 2022)
Coffee roasting is still using clay pans with the traditional method and heat is obtained from firewood fires. Only 20% of the national coffee bean production which reaches 600,000 tons per year is processed and marketed as secondary products. Treatment of temperature and roasting time can affect the physical mechanical properties of coffee, namely a faster decrease in water content, an increase in brittleness and an acceleration of color change. Adding the function of regulating the rotation speed of the stirrer on the horizontal roaster prototype while still emphasizing the traditional method equipped with temperature and time control to improve product creation. At a temperature of 12000 C coffee has not shown the level of maturity where the weight has not been very well reduced and there is no smell of aroma. Roasted maturity occurred at 18000 C for 15 minutes with a rotation of 100 RPM causing a significant weight loss of 60% and a strong aroma of coffee has been smelled. At a temperature set to 22000 C although the time and rotation varied, resulting in a completely burnt and immature coffee exhibited by a weight loss of only 50%. The results showed that temperature, time and rotation greatly affect the quality of roasting results.